Gabriele D’Annunzio and Two Contemporary Art Projects - Badurina, Natka (Poznańskie Studia Slawistyczne, 2019)
The centennnial of D’Annunzio’s occupation of Rijeka (September 1919 – January 1921) confronts the professions dealing with it – historiography, memory studies, public history, cultural management – with the problem of very different, often conflicting and mutually exclusive interpretations. The process of defining national borders after World War I, territorial claims and the unrealised plans of a new social order are parts of this historical episode still preoccupying interpreters. Here we will try to explain how D’Annunzio’s rule in Rijeka came to be interpreted in view of its similarity to the western hippie movement of 1968, and we will describe two recent artistic products of that interpretation: projects by Janez Janša (Il porto dell’amore) and Damir Stojnić (1:1). Both are interactive urban interventions in the city of Rijeka, and the latter is directly linked to the Rijeka – European Capital of Culture 2020 project.